English Noun Phrases from a Functional-Cognitive Perspective: Current issues - Sommerer, Lotte; Keizer, Evelien (John Benjamins Publishing Company, 2022)
Despite a significant increase in interest over the last two decades in the English Noun Phrase, there are still many open questions and unexplored issues. The papers collected in this volume contribute to this ongoing research by addressing a range of topics concerning the internal structure, use and development of English Noun Phrases. The eleven chapters represent three main themes: 1. Determination, modification and complementation; 2. Shell nouns and the X-is construction; 3. Binominal constructions. These topics are approached in different ways: some chapters are synchronic in nature, others diachronic; and while most subscribe to functional-cognitive modelling, some take a more formal approach. In addition, different methodologies are employed, varying from qualitative and quantitative corpus analyses to experimental methods. As a result, the contributions to this volume represent both the main topics currently discussed in research on the English Noun Phrase, and the diversity in the way these topics are investigate
Keywords: English linguistics; Germanic linguistics; Morphology; Syntax; Theoretical linguistics